Peningkatan Kemampuan Penyusunan Rencana Pelaksanaan Pembelajaran Guru MIN Amkoteng melalui Supervisi Akademik - Berkati, Berkati (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this study was to determine the increase in the ability of teachers in preparing Learning Implementation Plans (RPP) through academic supervision. This research is a school action research with steps: planning, implementation, observation, and reflection. This research is planned to consist of two cycles. This research was carried out at MIN Amkoteng Subdistrict Anjir Muara, Barito Kuala District, South Kalimantan Province. Quantitative data analysis was used to determine the increase in the value of the practice of making RPP by teachers based on the standards set by the Ministry of National Education. The results of the study show that the teacher's ability to prepare RPP can be improved by academic supervision; collaboration between teachers and Supervisors of Primary Schools can be well established and useful in fostering teachers to improve their abilities in preparing RPP; the complete document II of the Education Unit (KTSP) MIN Amkoteng curriculum is complete, in the form of RPP collection documents; and this academic supervision can be used as a model in the following years in terms of drafting RPP, and can be used as an example for other schools.